THE ROLE OF YOUTH INFORMATION IN OVERCOMING TANTRUM IN TOD BY TOD BY THE EFFECT OF GADGETS - Anisa Aulia; Mrs Wahyunengsih, Melia Santi (CV. ADIBA AISHA AMIRA, 2022)
Tantrums are emotional outbursts marked by a child being stubborn, crying, screaming, defiant, or angry. Usually toddlers often experience tantrums caused by gadgets. In the environment around us, we often see things like this, especially in toddlers who already understand how to play gadgets. Many parents find it difficult to watch their toddlers playing with gadgets because they spoil their children too much. These tantrums can occur from various ages, but for toddlers who experience tantrums usually occur more often and are often caused by a gadget. Therefore, we must understand some good ways to reduce the increase in tantrums in toddlers. Because these tantrums can inhibit the growth of children under five and can have a negative impact on the health of children who have tntrum in their daily lives. This research was conducted to find out what the parents and the extension workers did when they saw the tantrums. With this research, it is hoped that parents out there can limit the use of gadgets for toddlers so that they don't get tantrums because of the impact of a gadget